Amelioration of Non-Alcoholic Steatohepatitis by Atractylodes macrocephala Polysaccharide, Chlorogenic Acid, and Geniposide Combination Is Associated With Reducing Endotoxin Gut Leakage - Leng, Jing; Tian, Hua-jie; Fang, Yi; Hu, Yi-yang; Peng, Jing-hua (Frontiers in Cellular and Infection Microbiology, 2022)
Gut-derived lipopolysaccharide (LPS) leaking through the dysfunctional intestinal barrier participates in the onset of non-alcoholic steatohepatitis (NASH) via triggering inflammation in liver. In the present study, ACG combination, consisting of Atractylodes macrocephala polysaccharide (A), Chlorogenic acid (C) and geniposide (G), was demonstrated to ameliorate NASH in mice, reduce hepatic LPS signaling and endotoxemia without decreasing the abundance of identified Gram-negative bacteria but through restoring the intestinal tight junctions. Our data indicated that inhibition on LPS gut-leakage by ACG combination contributes to its amelioration on NASH.